In-kind incentives and health worker performance: Experimental evidence from El Salvador - Pedro Bernal; Sebastian Martinez (Inter-American Development Bank (IDB), 2018)
Maintaining high standards of care from doctors, nurses and other health professionals is of critical importance for an effective and efficient health system. Yet deficient levels of health worker performance, including low effort, absenteeism, and lack of compliance with clinical guidelines, have been documented across numerous countries and contexts. In response, various pay-for-performance interventions that reward providers based on measures of quality of care and health outcomes have been tested, with mixed results. This study experimentally evaluates the effects of team in-kind incentives on health worker performance in El Salvador. Thirty-eight out of 75 community health teams were randomly assigned to receive in-kind incentives linked to performance over a 12-month period. All 75 teams received monitoring, performance feedback and recognition for their achievements, allowing us to isolate the impacts of the incentive. While both treatment and control groups exhibit improvements in performance measures over time, the in-kind incentives generated significant improvements in community outreach, quality of care, timeliness of care, and utilization of services after 12 months. Contrary to conventional knowledge, gains are largest for health teams at the bottom and top of the baseline performance distribution. These results suggest that even small in-kind incentives can be a powerful tool to improve health worker performance and may be a viable alternative to monetary incentives in certain contexts.
Keywords: I12; I15; I18; C93; 330; Pay for Performance; Performance Incentives; In-Kind; Team Incentives; Health Services; El Salvador